2021
DOI: 10.6018/reifop.456041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluar la creatividad y las funciones ejecutivas: propuesta para la escuela del futuro

Abstract: Se presenta un estudio que pretende proponer estrategias de intervención didáctica y de evaluación para desarrollar y mejorar el funcionamiento ejecutivo y la creatividad en el alumnado de secundaria. Dicho estudio parte del análisis de las variables creatividad y funciones ejecutivas (memoria de trabajo (actualización), planificación, inhibición (verbal y motora), flexibilidad y toma de decisiones) medidas a través del Test de pensamiento creativo de Torrance(creatividad), la Escala de inteligencia de Weschle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…However, in the current study a negative correlation was found that could explain the response to the underlying process in the Stroop-type tasks. In this way, our study coincides with that carried out by Sánchez-Macias et al [34], who found a negative correlation between creativity and verbal inhibition in their evaluation of high school students between 14 and 17 years old.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the current study a negative correlation was found that could explain the response to the underlying process in the Stroop-type tasks. In this way, our study coincides with that carried out by Sánchez-Macias et al [34], who found a negative correlation between creativity and verbal inhibition in their evaluation of high school students between 14 and 17 years old.…”
Section: Discussionsupporting
confidence: 93%